Los Modelos De Evaluación Aplicado Por Los Docentes Y Su Influencia En El Proceso De Enseñanza Aprendizaje De Los Estudiantes De Educación Básica Superior De La Unidad Educativa “El Empalme” Del Cantón El Empalme, PROVINCIA Del Guayas. - RAFAEL LUBER, PONCE CASTRO (2014)
By identifying evaluation models applied by teachers to develop teaching-learning process in students, we are focusing one of the most crucial problems in improving the quality of education given by the government and referred to attain one of the axes of good live. To determine the influence of evaluation models applied by teachers in the teaching-learning process of the students, will help to improve the teaching- learning process and the graduate profile. It becomes a priority need to train teachers in the applicability of evaluation models. The proposal aims to develop a scientific research becomes a reference point for determining evaluation models in order to develop efficiently the process of learning in students of the Education Unit "The Splice", Guayas Province. Its effectiveness lies in the evaluation models not only guarantee student learning if not contributing to their training, through participation, the main receiver and transmitter of knowledge. The assessment has become one of the key instruments to promote changes in the Institutions of Higher Basic Education; between the central aspects of the evaluation are the relationships between the profile of training and professional relevance, scientific - technical and social.